2011
DOI: 10.1667/rr2635.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of56Fe-Particle Cranial Radiation on Hippocampus-Dependent Cognition Depend on the Salience of the Environmental Stimuli

Abstract: Ionizing radiation reduces the numbers of neurons expressing activity-regulated cytoskeleton-associated protein (Arc) in the hippocampal dentate gyrus (DG). It is currently unclear if that change relates to cognitive function. We assessed the effects of 1 Gy of head-only ⁵⁶Fe-particle irradiation on hippocampus-dependent and hippocampus-independent fear conditioning and determined how those changes related to Arc expression within the DG. Irradiated mice that did not receive tone-shock pairings on day 1 showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Age-related changes in immediate early gene Activity-Regulated Cytoskeleton-Associated Protein ( Arc ) in the hippocampus have been reported [24]. Our work showed that head-only 56 Fe ion irradiation of two-month-old mice alters hippocampal expression of Arc [25, 26]. Arc expression has been used to provide important insight into the post-transcriptional infrastructure of gene expression involved in synaptic plasticity and memory [27] (for review, [28]).…”
Section: Introductionmentioning
confidence: 77%
“…Age-related changes in immediate early gene Activity-Regulated Cytoskeleton-Associated Protein ( Arc ) in the hippocampus have been reported [24]. Our work showed that head-only 56 Fe ion irradiation of two-month-old mice alters hippocampal expression of Arc [25, 26]. Arc expression has been used to provide important insight into the post-transcriptional infrastructure of gene expression involved in synaptic plasticity and memory [27] (for review, [28]).…”
Section: Introductionmentioning
confidence: 77%
“…Exposure to such radiation can potentially induce a wide range of neurological consequences, and in animals it has been repeatedly shown to induce cognitive impairment (1,5,6). Although the mechanisms underlying this radiation-induced cognitive impairment are not clearly understood, previous studies suggest that the pathogenesis likely depends on multiple factors and may involve chronic oxidative stress (7), depletion of neuronal precursor cells of the hippocampus (2,8,9), neuroinflammation (10,11), altered expression of the plasticity-related immediate early gene Arc (6,12,13) and impaired neurogenesis (10,14). Indeed, it has been shown that exposure to iron radiation impairs the proliferation of hippocampal neural precursor cells in mice, and that the reductions in the generation of new neurons correlates in time with cognitive impairments seen in these mice (10).…”
Section: Introductionmentioning
confidence: 99%
“…While it is well understood that radiation exposure induces impairments in hippocampal dependent cognitive performance (1,5,6,13), little is known about the molecular mechanisms underlying these changes and whether they are associated with radiation-induced alterations in synaptic properties of DGCs. Due to different pattern of energy deposition and ionization track structures, irradiation with proton, silicon or iron may each have very different effects on cells and the overall neurological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal sensitivity to radiation-induced cognitive injury is not limited to gamma irradiation and is also seen 2 weeks (Haley et al, 2012, 2013) or later (Shukitt-Hale et al, 2000; Villasana et al, 2010, 2011; Raber et al, 2011; Yeiser et al, 2013) following 56 Fe irradiation. In all these studies, the animals were trained and tested for hippocampal function following irradiation.…”
Section: Introductionmentioning
confidence: 99%